Improved Smoking Cessation Rates in a Pharmacist-Led Program Embedded in an Inflammatory Bowel Disease Specialty Medical Home. (December 2022) - Tse, Stacy Saithy; Sands, Bruce E.; Keefer, Laurie; Cohen, Benjamin L.; Maser, Elana; Ungaro, Ryan C.; Marion, James F.; Colombel, Jean-Frédéric; Itzkowitz, Steven H.; Gelman, Jessica; Dubinsky, Marla C.
Background: Cigarette smoking is associated with disease progression, poor outcomes, and increased biologic use in Crohn's Disease (CD). In this prospective study, we describe the structure and results of a pharmacist-driven smoking cessation program in an Inflammatory Bowel Disease (IBD) Specialty Medical Home. Methods: One pharmacist designed and implemented a collaborative drug therapy management (CDTM) program, which allowed the pharmacist to initiate and modify smoking cessation aids, monitor medication safety and efficacy, and provide behavioral counseling. Crohn's Disease patients who were current smokers and referred to the program were analyzed. Clinical and demographic data, disease activity, and smoking history were collected. The primary outcome was the proportion of patients in the enrolled group and the declined group who quit smoking at least once during the follow-up period. Secondary outcomes include demographic and clinical differences between enrolled and declined patients, and enrolled quitters and non-quitters. Results: Thirty-two patients were referred to the program and 19 participated. Over a median follow-up period of 305 [264-499] days, 42% (8/19) of enrolled patients quit smoking at least once. Fifteen percent (2/13) of declined patients quit smoking. Patients who continued to smoke had more instances of loss of response to a biologic, need to start a new biologic, or escalation of biologic therapy. The CDTM pharmacist was able to provide all necessary clinical services for smokers enrolled in the program. Conclusions: A pharmacist-led smoking cessation program in a specialty medical home is feasible. It may result in successful quit attempts and may optimize IBD medication use.